Developing a Versatile Arsenal: Novel Antimicrobials as Offensive Tools Against Pathogenic Bacteria - Junze Ma; Zheng Lu (Microorganisms)
The pervasive and often indiscriminate use of antibiotics has accelerated the emergence of drug-resistant bacterial strains, thus presenting an acute threat to global public health. Despite a growing acknowledgment of the severity of this crisis, the current suite of strategies to mitigate antimicrobial resistance remains markedly inadequate. This paper asserts the paramount need for the swift development of groundbreaking antimicrobial strategies and provides a comprehensive review of an array of innovative techniques currently under scrutiny. Among these, nano-antimicrobials, antimicrobials derived from ribosomal proteins, CRISPR/Cas-based systems, agents that undermine bacterial bioenergetics, and antimicrobial polysaccharides hold particular promise. This analysis gives special attention to CRISPR/Cas-based antimicrobials, scrutinizing their underlying mechanisms, exploring their potential applications, delineating their distinct advantages, and noting their likely limitations. Furthermore, we extend our exploration by proposing theoretical advancements in antimicrobial technology and evaluating feasible methods for the effective delivery of these agents. This includes leveraging these advances for broader biomedical applications, potentially revolutionizing how we confront bacterial pathogens in the future, and laying a foundation for extended research in multimodal therapeutic strategies.